MANAGEMENT OF CHILDREN RELATIONSHIP THAT GROW AND DEVELOP IN EXTENDED FAMILIES - Joyo Nur Suryanto Gono (Jurnal Ilmu Komunikasi, 2020)
The family is function and is responsible for the process of child development. Parents are required to provide physical needs, guide, care for children to become an independent human being and are responsible for him. Even so, there are some families who are forced to care for their children in the extended family. The problem "how does the difference in meaning, care, can lead to conflict between parents and other extended family members? The purpose to examine the meaning and communication experience of parents and extended family members who are actively involved in child care. The method is a phenomenological approach. Primary data obtained from indepth interviews. The result that parenting is done by parents in terms of physical, psychological and social aspects in the form of love, attention, communication, learning, and control. Parenting is more appropriate for biological parents than for other figures who only pay attention and meet the needs of children when biological parents are not at home, for example, because they are working. Conflict resolution in large families tends to use collaboration style, extended family members discuss a problem to be solved together. The style of resolving individual conflicts is not always applied in the realm of extended families. They tend to adjust to other family members, especially in the interests of children.